Erythrocyte, saliva and serum arginase activity with serum urea and estrogen levels in Akkaraman and Ivesi sheep in pregnancy and postpartum - Ozan, ST; Yaralioglu, S; Ileri, T; Halifeoglu, I (Tubitak Scientific & Technological Research Council Turkey, 1999)
Arginase (L-arginine amidino hydrolase E.C. 3.5.3.1) is an enzyme catalyzing the last stage of the Krebs-Henseleit cycle and, thus, converting arginine into urea and ornithine. Arginase also plays a part in protein and polyamine synthesis and is affected by hormones in terms of metabolic status. In the present study, erythrocyte, saliva, and serum arginase activity together with serum urea and estrogen levels were examined in Akkaraman and Ivesi sheep in pregnancy and postpartum. Comparisons were then made between the species. In pregnancy the urea level in saliva increased. However, the urea level in serum decreased. No clear difference was observed in the level of urea in the erythrocytes of pregnant sheep. In pregnancy, it was observed that the estrogen hormone level increased, but erythrocyte arginase activity did not change. The saliva arginase level increased in both species. When the species were compared, it was found that, both in pregnancy and postpartum, erythrocyte and saliva arginase activity in Akkaraman and Ivesi sheep had significantly increased, but the urea level in the saliva and estrogen level decreased. However, no change was found in the urea level of serum and erythrocyte in either species. In pregnancy, the increase in saliva arginase activity was probably caused by hormone actions. However, the erythrocyte arginase activity did not increase. This observation supports the hypothesis that arginase is synthesized by two different genes.
Akkaraman ve İvesi Koyunlarinda, Gebelikte ve Do?umdan Sonra Eritrosit, Tükürük ve Serum Arginaz Aktiviteleri ile Serum Üre ve Östrojen Düzeyleri
Keywords: pregnancy; postpartum; Akkaraman; Ivesi; arginase; urea; estrogen; serum; erythrocyte; saliva